2008
DOI: 10.1523/jneurosci.1963-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Inhibits Neuroplasticity Induction in Human Motor Cortex

Abstract: We investigated whether plasticity of human motor cortex (M1) is influenced by time of day, and whether changes in circulating levels of cortisol contribute to this effect. Neuroplasticity was induced using paired associative stimulation (PAS), involving electrical stimulation of left median nerve, paired with transcranial magnetic stimulation over the right M1 25 ms later (90 pairs at 0.05 Hz). Surface EMG was recorded from the left abductor pollicis brevis (APB) and first dorsal interosseous muscle. Cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(175 citation statements)
references
References 66 publications
(87 reference statements)
5
160
3
2
Order By: Relevance
“…Interestingly, we were also able to show that a component of the reduced plasticity was associated with changes in cortisol levels. This is interesting, as we have previously demonstrated that cortisol can modulate cortical plasticity (Sale, Ridding, & Nordstrom, 2008), and it is well known that preterm birth is associated with alterations in the HPA axis (Sullivan, Hawes, Winchester, & Miller, 2008). This study, again, provides evidence that NIBS techniques are useful tools for probing the pathophysiology of conditions associated with functional and behavioural deficits.…”
Section: Assessment Of the Capacity For Plasticitysupporting
confidence: 54%
“…Interestingly, we were also able to show that a component of the reduced plasticity was associated with changes in cortisol levels. This is interesting, as we have previously demonstrated that cortisol can modulate cortical plasticity (Sale, Ridding, & Nordstrom, 2008), and it is well known that preterm birth is associated with alterations in the HPA axis (Sullivan, Hawes, Winchester, & Miller, 2008). This study, again, provides evidence that NIBS techniques are useful tools for probing the pathophysiology of conditions associated with functional and behavioural deficits.…”
Section: Assessment Of the Capacity For Plasticitysupporting
confidence: 54%
“…Inconsistent treatment outcomes appear to be influenced by variability in individuals' responses to NIBS. Several factors have been shown to influence the reliability and effectiveness of NIBS (Ridding and Ziemann, 2010), including genetic factors (Cheeran et al, 2008, Antal et al, 2010, hormone and drug interactions (Sale et al, 2008), age (Rogasch et al, 2009;Todd et al, 2010;Bashir et al, 2014) and levels of physical activity ). Other important factors that appear critical in determining the brain's response to NIBS, and which will be discussed in detail in this review, are the site of stimulation (Fox et al, 2014) and the activity of the underlying networks during stimulation (Nitsche et al, 2003;Fregni et al, 2005;Hummel et al, 2005;Antal et al, 2007;Kujirai et al, 2006;Andrews et al, 2011).…”
Section: Brain Stimulation As a Clinical Intervention For Restoring Nmentioning
confidence: 99%
“…Controlling or minimizing some of the factors that contribute to this variability have been shown to improve the effectiveness and reliability of the induced effects (Sale et al, 2008;Kamke et al, 2014). However, the variability of the brain's response to rTMS remains a significant impediment to the application of such approaches in the clinical domain.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…For PAS, 90 paired peripheral and cortical stimuli were delivered at a frequency of 0.1 Hz (duration 15 mins). All experiments were performed at approximately the same time of day (~ 2pm) to minimise response variability due to circadian factors (Sale et al, 2007(Sale et al, , 2008.…”
Section: Paired Associative Stimulation (Pas)mentioning
confidence: 99%